Mineralogy, zircon U–Pb–Hf isotopes, and whole‐rock geochemistry of Late Cretaceous–Eocene granites from the Tengchong terrane, western Yunnan, China: Record of the closure of the Neo‐Tethyan Ocean. (27th July 2017) - Cao, Hua‐Wen; Zhang, Yun‐Hui; Santosh, M.; Zhang, Shou‐Ting; Tang, Li; Pei, Qiu‐Ming
Abstract : New data from mineralogy, geochemistry, zircon U–Pb dating, and Hf isotopes have revealed Late Cretaceous to Eocene magmatic intrusions in the Tengchong terrane and constrained the origin, tectonic setting, and characteristics of tin‐bearing and barren granitoids. We divide the studied granitoids into two groups: (a) the Late Cretaceous Zhinaxiang (70 Ma) and Early Paleocene Dazhupeng (65 Ma) S‐type barren granites and (b) the Eocene Lailishan A2 ‐type tin‐bearing granite (50 Ma). All these granitoids display Si‐ and K‐rich and calc‐alkaline characteristics and have similar chondrite‐normalized rare earth element patterns. However, geochemical differences do exist between the two groups of granites. The Zhinaxiang and Dazhupeng S‐type granites are slightly peraluminous, enriched in large‐ion lithophile elements (e.g., Rb and K), and depleted in high‐field‐strength elements (e.g., Nb, Ta, Zr, and Hf), whereas the Lailishan A2 ‐type granite has higher T Fe2 O3, high‐field‐strength element content, and Ga/Al ratios. The geochemical and Hf isotopic data indicate that the granites in this study were generated by partial melting of Paleoproterozoic metasedimentary rocks. Due to the subduction of the Neo‐Tethyan Ocean beneath the Eurasian plate, the Zhinaxiang and Dazhupeng S‐type granites were formed in a thickened‐crustal environment, whereas the Lailishan A2 ‐type granite was emplaced in a post‐collisional extensional setting attributed to slab break‐off. By comparison between tin‐bearing and barren granites, we propose that the Sn mineralization could be related to relatively high‐temperature and low‐pressure crystallization conditions.